The Effect of the Cooperative Learning Method (Student Team Learning) on Students’ Collaboration Skills in Islamic Education PAI at SMPN 2 Rengasdengklok - Hasna Fadlilatul Maula Hasna; Iqbal Amar Muzaki; Masykur H. Mansyur (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the effect of the cooperative learning method, Student Team Learning (STL), on the collaboration skills of seventh-grade students in Islamic Education at SMPN 2 Rengasdengklok. The research employed a quantitative correlational approach. The sample consisted of 40 students selected through simple random sampling. Data were collected using Likert-scale questionnaires and documentation, and analyzed using simple linear regression with SPSS version 25. The results indicate a positive and significant effect of STL on students’ collaboration skills, with a regression coefficient of 0.748 and a significance value of 0.000.